Avaliação do crescimento e da qualidade da madeira de clones de Eucalyptus em dois ambientes para produção de celulose - Freitas, Thaís Pereira (2015)
The eucalyptus wood plantations is the main source of material for the production of bleached pulp in Brazil, which currently holds the position of the largest producer of hardwood pulp in the world. It is known that the place of growth may influence the growth plant and consequently the wood properties that is being formed. Thus, the objective of this work was to evaluate the environment ffect on growth and wood technological characteristics in Eucalyptus grandis x Eucalyptus urophylla clones to pulpwood. The studied clones were derived from clonal test plantations of the Fibria Celulose S.A. company, in two locations, Nova Almeida – ES and Posto da Mata – BA, with 6,5 years old. It was evaluated the wood anatomical and chemical characteristics, the specific gravity, the kraft pulping parameters, and the correlations between some of these characteristics employing the Pearson correlation matrix 1% of significance. Among the evaluated parameters, the heartwood and sapwood were the only features that showed no influence of growing location for all the studied clones. The timber volume, the specific gravity, the fiber wall thickness and the syringyl:guaiacyl lignin ratio were the characteristics considered more stable to environment changes. A significant negative correlation between specific gravity with yield pulping and the consumption specific apparent of wood for pulpwood was observed, and also a trend of decreased syringyl:guaiacyl lignin ratio with increasing basic density.